Controlled ovarian stimulation should not be preferred for male infertility treated with intrauterine insemination: a retrospective study - Yan Tang; Qian-Dong He; Ting-Ting Zhang; Jing-Jing Wang; Si-Chong Huang; Yun Ye (BMC, 2021)
Abstract Background Some studies have stated that intrauterine insemination (IUI) with controlled ovarian stimulation (COS) might increase the pregnancy rate, while others suggest that IUI in the natural cycle (NC) should be the first line of treatment. It remains unclear whether it is necessary to use COS at the same time when IUI is applied to treat isolated male factor infertility. Thus, we aimed to investigate efficacy of IUI with COS for isolated male factor infertility. Methods A total of 601 IUI cycles from 307 couples who sought medical care for isolated male factor infertility between January 2010 and February 2020 were divided into two groups: NC-IUI and COS-IUI. The COS-IUI group was further divided into two subgroups according to the number of pre-ovulatory follicles on the day of HCG: cycles with monofollicular development (one follicle group) and cycles with at least two pre-ovulatory follicles (≥ 2 follicles group). The IUI outcomes, including clinical pregnancy, live birth, spontaneous abortion, ectopic pregnancy, and multiple pregnancy rates were compared. Results The clinical pregnancy, live birth, spontaneous abortion, and ectopic pregnancy rates were comparable between the NC-IUI and COS-IUI group. Similar results were also observed among the NC-IUI, one follicle, and ≥ 2 follicles groups. However, with respect to the multiple pregnancy rate, a trend toward higher multiple pregnancy rate was observed in the COS-IUI group compared to the NC-IUI group (8.7% vs. 0, P = 0.091), and a significant difference was found between the NC-IUI and ≥ 2 follicles group (0 vs. 16.7%, P = 0.033). Conclusion In COS cycles, especially in those with at least two pre-ovulatory follicles, the multiple pregnancy rate increased without a substantial gain in overall pregnancy rate; thus, COS should not be preferred in IUI for isolated male factor infertility. If COS is required, one stimulated follicle and one healthy baby should be the goal considering the safety of both mothers and foetuses.